2019
DOI: 10.1002/ece3.4987
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of the xerophytic genus Anabasis L. (Chenopodiaceae)

Abstract: Aim Using the extremophile genus Anabasis, which includes c. 28 succulent, xerophytic C4 species, and is widely distributed in arid regions of Northern Africa, Arabia, and Asia, we investigate biogeographical relationships between the Irano‐Turanian floristic region (ITfr) and its neighboring regions. We test whether the spread of arid and semi‐arid biomes in Eurasia coincides with the biogeography of this drought‐adapted genus, and whether the ITfr acted as source area of floristic elements for adjacent regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(102 reference statements)
2
11
0
Order By: Relevance
“…The "southern route” scenario: Mediterranean steppes are thought to be descendants of the Anatolian steppes that expanded throughout the Mediterranean during the Pliocene (Suc et al., 2018 ). This route, however, is discussed for xeric steppe elements only (Jia & Bartish, 2018 ; Lauterbach et al., 2019 ; Manafzadeh et al., 2014 ; Žerdoner Čalasan et al., 2021 ), and Capsella does not belong to this ecological group. The main argument against an Early Pliocene southern Capsella route is the estimated divergence time between the two basally branching lineages, the Mediterranean C. grandiflora/rubella and the continental C. orientalis lineage of ca.…”
Section: Discussionmentioning
confidence: 99%
“…The "southern route” scenario: Mediterranean steppes are thought to be descendants of the Anatolian steppes that expanded throughout the Mediterranean during the Pliocene (Suc et al., 2018 ). This route, however, is discussed for xeric steppe elements only (Jia & Bartish, 2018 ; Lauterbach et al., 2019 ; Manafzadeh et al., 2014 ; Žerdoner Čalasan et al., 2021 ), and Capsella does not belong to this ecological group. The main argument against an Early Pliocene southern Capsella route is the estimated divergence time between the two basally branching lineages, the Mediterranean C. grandiflora/rubella and the continental C. orientalis lineage of ca.…”
Section: Discussionmentioning
confidence: 99%
“…1 ) in particular serving as a center for plant diversification since at least the early Miocene [e.g., ( 3 , 117 )]. Molecular phylogenetic analyses reveal that diversification in both the alpine biome [e.g., ( 3 , 118 )] and steppe-desert lowlands ( 119 121 ) occurred during the mid- to late Miocene, which appear to be driven mainly by cooling and progressive aridity, respectively. This may be related to the generalized northward expansion of the Tibetan Highland and mountain ranges in the vicinity, including uplift of the Tian Shan, Pamir, Kunlun, and Qilian Shan-Nan Shan ( 122 , 123 ).…”
Section: Drivers Of Neogene Recovery To Modern Steppe-desertmentioning
confidence: 99%
“…As has been discussed above, the genus might have experienced an early rapid radiation during the middle to late Miocene, as major lineages of the genus arose in a short timescale between 11 and 7 Ma, which is consistent with the origin and diversification of other taxa distributed in the Asian interior arid‐zone flora such as Ephedra L. (Ephedraceae; Qin et al., 2013), Caragana Fabr. (Fabaceae; Zhang et al., 2016), Astragalus L. (Fabaceae; Azani et al., 2019), and Anabasis L. (Amaranthaceae; Lauterbach et al., 2019). Pollen records also demonstrated that herbs first become widespread in Central Asia at ca.…”
Section: Discussionmentioning
confidence: 99%